2021
DOI: 10.1007/s00203-021-02700-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and probiotic potential of lactic acid bacteria from swine feces for feed additive composition

Abstract: Animal microbiota is becoming an object of interest as a source of beneficial bacteria for commercial use. Moreover, the escalating problem of bacterial resistance to antibiotics is threatening animals and humans; therefore, in the last decade intensive search for alternative antimicrobials has been observed. In this study, lactic acid bacteria (LAB) were isolated from suckling and weaned pigs feces (376) and characterized to determine their functional properties and usability as pigs additives. Selection of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Furthermore, the levels of proteolysis closely paralleled those observed in probiotics isolated from other species, such as cattle, where indices of proteolytic activity were analogous (0.2–0.6) ( Ramadhan et al , 2021 ). Conversely, an inquiry into probiotics isolated from pig feces revealed proteolytic halos with a maximum diameter of 3 mm following 24 hours of incubation ( Marchwińska and Gwiazdowska, 2022 ). Another investigation focused on probiotics obtained from sheep dairy products reported protein hydrolysis diameters exceeding 10 mm ( Silva et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the levels of proteolysis closely paralleled those observed in probiotics isolated from other species, such as cattle, where indices of proteolytic activity were analogous (0.2–0.6) ( Ramadhan et al , 2021 ). Conversely, an inquiry into probiotics isolated from pig feces revealed proteolytic halos with a maximum diameter of 3 mm following 24 hours of incubation ( Marchwińska and Gwiazdowska, 2022 ). Another investigation focused on probiotics obtained from sheep dairy products reported protein hydrolysis diameters exceeding 10 mm ( Silva et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the LAB strains isolated from the intestine of freshwater fish species exhibited amylase, lipase, and protease activities [ 84 ]. Similarly, Marchwiska and Gwiazdowska [ 87 ] reported that different Lactobacillus and Pediococcus isolated from swine faeces for feed additive composition had protease and amylase activities, but no lipase activity. Bacillus species have already been known as enzyme producers, being one of the reasons for their use in aquaculture as probiotics enhancing feed digestibility, digestive enzyme activities, and growth performance [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…All 42 tested strains had a growth inhibition coefficient below 0.5 (Table V), indicating good tolerance to bile salts (Liu et al 2021). Marchwińska and Gwiazdowska (2021) stated that the content of bile salt caused a decrease in bacterial survival; however, for many of the strains studied by these authors, no statistically significant differences in growth were observed in the presence of 0.5 and 1% bile salt. In turn, in the studies carried out by Kowalska et al (2020) and Śliżewska et al (2021), most of the tested strains survived in an environment with a concentration of up to 2% bile salt.…”
Section: Lacticaseibacillusmentioning
confidence: 91%
“…New potentially probiotic strains 3 405 3 406 also showed a weak antagonistic effect compared to the reference strain L. rhamnosus ATCC® 53103™. According to Marchwińska and Gwiazdowska (2021), not all lactic acid bacteria inhibit the growth of pathogenic bacteria; 87 out of 376 isolates did not show such properties. Due to the lack of inhibition of the growth of pathogenic microorganisms, these strains do not have all the properties normally associated with probiotic strains.…”
Section: Lacticaseibacillusmentioning
confidence: 99%